Illicit trafficking of cultural properties in Arab states - Khabour, Anas Al, (Archaeopress Archaeology, 2022)
Offering an overview of the phenomenon of illicit trafficking of cultural properties, this book serves as a reference point for governments, enforcement agencies, international organizations, stakeholders, and civil societies. The geographic focus is the Arab World: the countries in the Middle East, Gulf of Arabia, Horn of Africa and North Africa.